PEMIKIRAN POLITIK HASAN AL-BANNA - Dewi, Rusmala (Universitas Islam Negeri Raden Fatah Palembang, 2015)
Abstract: Hasan al Banna, one of Islamic prominent figures,was born at the end of 20 tahun century. His ideas andmovement together with ikhwanul Muslimin had arousedfighting spirit of Islamic society in order not be left behind.Returning to the life inspired by al-quran and as sunnah is themission of the movement led by Hasan al Banna. Although thisIslamic renewal figure had passed away, his thoughts still existin Islamic society’s life. Therefore, Hasan al-Banna’s thoughtswill be discussed in this article especially his political ideas .ملخص: ولد حسن البنا، واحدة من الشخصیات البارزة الإسلامیة ، في نھایة القرن20 . قد أفكاره و الحركة جنبا إلى جنب مع